A differential scanning calorimetric (DSC) study on the effects of annealing and sugars-emulsifiers on gelatinization of sago starch (Metroxylon sagu) - Abd Ghani, Maaruf B.; Che Man, Yaakob B.; Mat Hashim, Dzulkifly; Abd Rahman, Russly (Blackwell Publishing, 1999)
This study investigated the effects of annealing, at different temperatures (45-70C), times (0-24 h) and water:starch ratios (0.6/1-4/1), on the DSC thermal properties profiles associated with gelatinization temperatures of sago starch-water mixtures. The effects of sugars-emulsifiers and of starch mixtures and their interactions were also investigated. DSC data showed an increased gelatinization temperature and enthalpy and a narrower gelatinization temperature range (Tm-To) after annealing of sago starch; the extent of these changes was inversely proportional to the degree of crystallinity of the native starch. For sago starch, the G transition occurring at about 66-69C and the M1 transition occurring at about 75C in excess water became broader and shifted to higher temperatures as the water content was decreased. The effects on the gelatinization temperature and ΔH, of the addition of sugars-emulsifiers to the starch-water mixture, were observed by comparison with the starch-water results. Sucrose raised the gelatinization temperature by about 6-7C more than did glucose, for sago starch. Emulsifiers (sucrose ester and polysorbate-60), in the presence of sucrose or glucose, did not affect the gelatinization temperature.